AN ASSESSMENT OF COLIFORM BACTERIA IN THE RIVER MAHANADI SYSTEM OF SAMBALPUR - MEERAMBIKA MISHRA; , AMIYA KUMAR PATEL; NIRANJAN BEHERA (The Bioscan, 2012)
The study evaluates the status of coliform bacteria in the River Mahanadi in Sambalpur. Water samples from 12 different sites were collected for bacteriological analysis in order to assess its potability. The data exhibited total coliform count ranging from 11 to 2400 MPN per 100mL of water at 37°C. The faecal coliform count varied from 04 to above180 MPN per 100mL of water across the sites. The higher levels of coliform counts were consistently found in almost all samples collected from different sites. Besides, Klebsiella sp., Enterobacter aerogenes, Proteus vulgaris and Shigella sp. were also detected along with E. coli in the water samples. The findings suggested that the water from different sites in Ayodhya Saro var, Mahanadi did not meet the World Health Organization Standards for drinking water and should therefore be treated before consumption.